Five-year follow-up after transcatheter aortic valve implantation for symptomatic aortic stenosis. Issue 24 (6th July 2017) - Zahn, Ralf; Werner, Nicolas; Gerckens, Ulrich; Linke, Axel; Sievert, Horst; Kahlert, Philipp; Hambrecht, Rainer; Sack, Stefan; Abdel-Wahab, Mohamed; Hoffmann, Ellen; Zeymer, Uwe; Schneider, Steffen
Abstract : Objectives: Transcatheter aortic valve implantation (TAVI) has been implemented into the care of elderly patients suffering from severe symptomatic aortic stenosis. However, data on long-term follow-up are sparse and predictors of long-term mortality need to be evaluated to better select patients. Therefore, we aimed to analyse predictors of 5-year mortality after TAVI. Methods: We analysed data from the German Transcatheter Aortic Valve Interventions—Registry. Each of the 27 participating hospitals agreed to include all consecutive TAVI patients at their institution. Out of 1444 patients treated with TAVI, 1378 patients had a follow-up of at least 4.5 years (completeness 95.4%). Endpoint for this analysis was 5-year survival. Cox regression analysis was used to determine risk factors associated with this endpoint. Results: Patients who died were compared with survivors. The two groups showed multiple differences in patient characteristics, indications for interventions, preinterventional, as well as interventional characteristics and postinterventional events. Calculated 1-year mortality was 21.8% and 5-year mortality 59.1%. A higher logistic EuroScore was associated with a lower 5-year survival, being 45.5% in patients with a logistic EuroScore of <20%, 34.5% in those with 20% to 40% and 28.4% in patients with a logistic EuroScore >40%. Cox proportional hazard analysis revealed the following independent predictors of 5-year mortality: female gender (HR =0.66, 95% CI 0.56 to 0.77, p<0.0001), renal failure (HR=1.43, 95% CI 1.22 to 1.69, p<0.0001), prior mitral regurgitation ≥II° (HR=1.42, 95% CI 1.21 to 1.65, p<0.0001), residual aortic regurgitation ≥II° (HR=1.52, 95% CI 1.24 to 1.85, p<0.0001), atrial fibrillation (HR=1.38, 95% CI 1.18 to 1.64, p=0.0001), low gradient aortic stenosis (HR=1.48, 95% CI 1.19 to 1.84, p=0.0004), prior decompensation (HR=1.32, 95% CI 1.13 to 1.54, p=0.0006), frailty (HR=1.31, 95% CI 1.09 to 1.58, p=0.004), surgical TAVI (HR=1.42, 95% CI 1.12 to 1.80, p=0.004), age (by year) (HR=1.02, 95% CI 1.01 to 1.03, p=0.006), prior myocardial infarction (HR=1.29, 95% CI 1.07 to 1.57, p=0.009), urgent TAVI (HR=1.25, 95% CI 1.04 to 51, p=0.020) and diabetes mellitus (HR=1.20, 95% CI 1.02 to 1.40, p=0.024). Conclusions: These data from the early TAVI experience show a 5-year mortality of 59.1%. Some of the predictors of 5-year mortality seem to be modifiable, such as residual aortic regurgitation, type of TAVI access route and concomitant mitral regurgitation.